1990
DOI: 10.1104/pp.94.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and Respiratory Activity of Fruiting Forms within the Cotton Canopy

Abstract: The supply of photosynthates by leaves for reproductive development in cotton (Gossypium hirsutum L.) has been extensively studied. However, the contribution of assimilates derived from the fruiting forms themselves is inconclusive. Field experiments were conducted to document the photosynthetic and respiratory activity of cotton leaves, bracts, and capsule walls from anthesis to fruit maturity. Bracts achieved peak photosynthetic rates of 2.1 micromoles per square meter per second compared with 16.5 micromole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
16
0
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 16 publications
7
16
0
3
Order By: Relevance
“…Stomatal conductance has been reported to greatly decrease under limited water supply conditions [23,24]. Experiments with potted plants have reported that water-deficit stress decreased cotton leaf stomatal conductance [25,26]. In our study, in accordance with the majority of the previous research, significant decreases in leaf stomatal conductance rates of waterstressed plants were observed compared to the control.…”
Section: Discussionsupporting
confidence: 81%
“…Stomatal conductance has been reported to greatly decrease under limited water supply conditions [23,24]. Experiments with potted plants have reported that water-deficit stress decreased cotton leaf stomatal conductance [25,26]. In our study, in accordance with the majority of the previous research, significant decreases in leaf stomatal conductance rates of waterstressed plants were observed compared to the control.…”
Section: Discussionsupporting
confidence: 81%
“…Whereas this balance of CO2 fluxes may occur in certain legume and grain crops, previous studies have indicated that cotton fruit do not assimilate CO2 from the ambient atmosphere (8,16,23). This lack of CO2 assimilation was recently shown by Wullschleger and Oosterhuis (23) to be related not to an impaired photosynthetic capacity but rather to an overwhelmingly large CO2 gradient from the fruit interior (0.45-1.53% C02, v/v) to the external atmosphere.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, a combination of CO2 exchange, stable C isotope, and chlorophyll (Chi) fluorescence techniques were used to examine the recycling of atmospheric C02, these organs nonetheless frequently demonstrate a unique capacity for the reassimilation of internally produced C02, especially that CO2 released via mitochondrial respiration from developing ovules (4, 9). Cereal crops have received the greatest attention in this regard (5, 14, 25), although several studies have dealt with other crops as well (2,11,15,16,23). The efficiency with which fruit are able to conserve respired C for subsequent retranslocation back to the ovule could be an important determinant of yield productivity ( 11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations